Analysis of Factors Affecting the Volume Of Sugar Imports in Indonesia in 2017-2019 - Kristiana, Novia Tri; Raj, Keerthan (Yayasan Sinergi Kawula Muda, 2023)
The objective of this study is to analyze the result of data of sugar production and gross domestic product (GDP) to volume of import of sugar in Indonesia. This study used quantitative research method. The data used in this study is secondary data. Sample was determined using random sampling method. The data processing technique used multiple linear regression method with the use of eviews version 12 application. Result of this study identified that production amount not affecting significantly to volume of import of sugar in Indonesia, it was shown with probability value 0.010> 0.05, Gross Domestic Product (GDP) has significant influence to volume of import of sugar in Indonesia identified with probability value 0.00 < 0.005.